Parental Renovascular Hypertension-Induced Autonomic Dysfunction in Male Offspring Is Improved by Prenatal or Postnatal Treatment With Hydrogen Sulfide - Guo, Qi; Feng, Xiaohong; Xue, Hongmei; Jin, Sheng; Teng, Xu; Duan, Xiaocui; Xiao, Lin; Wu, Yuming (Frontiers in Physiology, 2019)
Increasing evidence indicates there is a strong association between parental health during pregnancy and incidence of cardiovascular disease in adult offspring. Recently, hydrogen sulfide (H2S) has been demonstrated to be a powerful vasodilator of the placental vasculature, improving intrauterine growth restriction. In this study, we investigated whether parental hypertension induces autonomic dysfunction in male adult offspring, and the H2S mechanism underlying this autonomic dysfunction. 2-kidney-1-clip method was employed to induce parental hypertension during pregnancy and lactation in rats. Basal blood pressure (BP) and autonomic function of male offspring in adulthood was evaluated. Additionally, either maternal hypertensive dams or their male offspring after weaning were treated with H2S to determine improving effects of H2S on autonomic dysfunction. The BP was significantly increased in male offspring of renovascular hypertensive dams when compared to that in offspring of normotensive dams. The offspring of renovascular hypertensive dams also exhibited blunted baroreflex sensitivity, increased sympathetic effect and sympathetic tonus. Western blotting analysis revealed downregulation of endogenous H2S catalyzed enzyme and upregulation of angiotensin Ang II type 1 receptor (AT1R) pathway in the nucleus tractus solitarius and rostral ventrolateral medulla, two hindbrain nuclei involved in BP and autonomic regulation, in these offspring. Either prenatal or postnatal treatment with H2S improved the adverse effects. The results suggest that parental hypertension results in elevated BP and autonomic dysfunction in adult male offspring through activation of AT1R pathway and inhibition of endogenous H2S production in the brain.